Developing Information Literacy Models for Special Needs Students: A Case Study in Bengkulu, Indonesia - Samosir, Fransiska Timoria; Ginting, Richard Togaranta; Ivone, Belia Lady (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
Information literacy is a critical skill for all students, including those with disabilities, to access and utilize knowledge effectively. This study explored the information literacy practices of students with disabilities and developed a tailored information literacy model to address their unique needs. Conducted at the State Special School of 1 Bengkulu, Indonesia (Sekolah Luar Biasa Negeri 1 Bengkulu), this research employs a qualitative descriptive approach. Data were collected through interviews, observations, and document analysis, with participants including students with disabilities and their educators. The study revealed that students heavily rely on teachers for accessing information, utilizing sources such as books, libraries, the internet, and museums. However, their information literacy skills remain underdeveloped due to challenges associated with their disabilities. Based on these findings, the study proposed a model designed to enhance information literacy by guiding students in identifying, searching, evaluating, and effectively using information. This model aims to foster greater independence and adaptability in accessing and processing information, contributing to equitable education outcomes for students with disabilities.